2014
DOI: 10.1021/ja4131142
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Selenolate-Protected Au24(SeR)20 Nanocluster

Abstract: We report the X-ray structure of a selenolate-capped Au24(SeR)20 nanocluster (R = C6H5). It exhibits a prolate Au8 kernel, which can be viewed as two tetrahedral Au4 units cross-joined together without sharing any Au atoms. The kernel is protected by two trimeric Au3(SeR)4 staple-like motifs as well as two pentameric Au5(SeR)6 staple motifs. Compared to the reported gold-thiolate nanocluster structures, the features of the Au8 kernel and pentameric Au5(SeR)6 staple motif are unprecedented and provide a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
172
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 32 publications
7
172
0
1
Order By: Relevance
“…13−16 Among them, gold clusters have been studied extensively. Crystal structures of several gold clusters such as Au 23 , 17 49 and Ag 44 33 have been reported, whereas only one alloy, namely, Cu n Au 25−n (n = 1−9), 50 is known with such monolayers. So far, to the best of our knowledge, there is no report on Ag−Pd alloy clusters.…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 99%
“…13−16 Among them, gold clusters have been studied extensively. Crystal structures of several gold clusters such as Au 23 , 17 49 and Ag 44 33 have been reported, whereas only one alloy, namely, Cu n Au 25−n (n = 1−9), 50 is known with such monolayers. So far, to the best of our knowledge, there is no report on Ag−Pd alloy clusters.…”
Section: Section: Physical Processes In Nanomaterials and Nanostructuresmentioning
confidence: 99%
“…To date, icosahedral, face-centered-cubic (FCC)-ordered and smaller Au core ( < 13 Au atoms) structures have been reported crystallographically for various Au n (SR) m sizes [19,[21][22][23][24][25][26][27][28][29][30]. A couple of selenolate-protected Au NCs have also been recently elucidated with icosahedral or small Au 8 core structures [31,32]. In the last few years, a number of surface structures in addition to the monomeric and dimeric staple-like motifs were identified such as a trimeric staple-like motif [28], tetrameric staple-like motif [29,30], μ 3 sulfide coordination [25], bridging thiolate motif [24], and ring-like motifs (long Au-SR oligomers) [27,33].…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
“…Figure 1 presents the diversity of thiolate-protected Au NC structures. Currently, only the dimeric staple-like motif and ring-like motif have been confirmed to exist in structurally analogs selenolate-protected Au NCs [31,32].…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%
“…Previously, Jin et al reported a thiolate protected Au 19 cluster with a composition of Au 19 (SCH 2 CH 2 Ph) 13 based on mass spectrometry, 28 and Jiang predicted from density functional theory (DFT) that this cluster has a defective icosahedral Au 11 core wrapped by two RS−Au−SR and three RS−Au−SR−Au−SR staple motifs. 29 But its experimental structure is still unknown.…”
mentioning
confidence: 99%